E-LEARNING BERBASIS MOODLE SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA DITINJAU DARI PEMAHAMAN MAHASISWA - Asri Fauzi; Aisa Nikmah Rahmatih (IKIP Siliwangi, 2021)
The purpose of this study is to determine the effectiveness of Moodle-based e-learning which is used as a learning medium in terms of student understanding. This type of research is quantitative quasi-experimental research with a one group pretest posttest design. The population of this study was 2nd-semester students. The sample of this research was 36 students who were taken based on cluster random sampling technique. This research instrument uses math test questions that can be accessed through e-learning. The data analysis techniques were normality test as a prerequisite test, test for the difference in average pretest and posttest, test for the increase in the pretest and posttest results (N-Gain), and finally the effect size test. The results showed that the pretest data were not normally distributed, while the posttest data were normally distributed so that nonparametric statistical tests were carried out. The nonparametric statistical test used is the Wilcoxon test where the results show a sig score. (0.00) <0.05, which means that there is a difference between the average pretest and posttest scores. Furthermore, the n-gain test was carried out with a score of 0.53 which was in the medium category. This means that the pretest and posttest scores have a moderate level of improvement. And the last test results with the effect size test with a score of d = 1.47 which is in the strong effect category. This means that Moodle-based e-learning has a strong effect on students' understanding of mathematical concepts.